2009
DOI: 10.1007/978-3-642-03655-2_30
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of User Interface Design and Input Methods for Applications on Mobile Touch Screen Devices

Abstract: Abstract. With the advent of touch screen phones, good UI design and simplified input methods for applications running on such devices are important factors that contribute to its popularity and success. The goal of this research is to evaluate different user interface designs and input methods for mobile phones with touch screen capability. In order to do this, two prototypes of a simple social networking application were implemented using a G1 phone that runs the Android platform. A user study has been condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…There were only few studies that compared different input forms. Balagtas-Fernandez et al [113] assessed two layouts (i.e., scrolling list and tabs), two input methods (i.e., keyboard and modal dialogue), and two menu designs (i.e., device menu and context menu). The results indicated that the scrolling, modal dialogue, and the device menu were more efficient [113].…”
Section: Input Mode and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were only few studies that compared different input forms. Balagtas-Fernandez et al [113] assessed two layouts (i.e., scrolling list and tabs), two input methods (i.e., keyboard and modal dialogue), and two menu designs (i.e., device menu and context menu). The results indicated that the scrolling, modal dialogue, and the device menu were more efficient [113].…”
Section: Input Mode and Selectionmentioning
confidence: 99%
“…Balagtas-Fernandez et al [113] assessed two layouts (i.e., scrolling list and tabs), two input methods (i.e., keyboard and modal dialogue), and two menu designs (i.e., device menu and context menu). The results indicated that the scrolling, modal dialogue, and the device menu were more efficient [113]. El Batran and Dunlop [114] compared two form navigation methods: tabbing and pan and zoom.…”
Section: Input Mode and Selectionmentioning
confidence: 99%
“…• Mobile device user interfaces (UI) which provide a new mechanism of human computer interaction sequences such as multi-touch interfaces, image recognition, code scanning, etc… that have not been previously explored in research and there is not any established user interface guidelines exist [2,4].…”
Section: Challenges Of M-learningmentioning
confidence: 99%
“…Different GUI designs and input methods for touch-based mobile phones are investigated in [7], focusing on overall interface layout (scrollable vs. tabbed GUI), input mode (keyboard vs. tapping through a modal dialog) and menu access (device menu vs. context menu). The two GUIs under study in [7] differed in all these characteristics, which were investigated through an assigned task.…”
Section: Related Workmentioning
confidence: 99%
“…The two GUIs under study in [7] differed in all these characteristics, which were investigated through an assigned task. Nevertheless, it is hard to prove that only the investigated characteristic accounts for slower performance and that there is no influence from other characteristics.…”
Section: Related Workmentioning
confidence: 99%